KARAKTERISASI BAKTERI PENGHASIL ASAM INDOL ASETAT DAN PENGARUHNYA TERHADAP VIGOR BENIH PADI - Lestari, Puji; Suryadi, Yadi; Susilowati, Dwi Ningsih; Priyatno, Tri Puji; Samudra, I Made (Research Center for Biology-Indonesian Institute of Sciences, 2015)
The ability to produce indole acetic acid (IAA) by endophytic bacteria is one of the basic criteria for the use of bacteria as plant growth promoter agent which is essential for the agricultural production.The objectives of this study were to evaluate the ability of 17 bacterial isolates to produce IAA and its effect on improvement of rice seed germination and molecular identification of the selected isolates based on the 16S rRNA gene. The IAA content was determined using Salkowski method measured by spectrophotometer UV-Vis and the effect of endophytic bacteria inoculation on seed germination was done by in vitro assay. Sequences of the selected isolates 16S rRNA amplified by PCR were analyzed the homology against bacterial 16S rRNA database in Genebank. IAA values ranged from 6.632 to 50.053 mg/L with the highest IAA production shown by isolate 6KJ which was followed by 4PB (41.807 mg/L). Bacterial IAA increased rice seed vigor significantly compared to control. However, bacterial inoculation with different concentrations of IAA did not significantly affect the growth of rice plants. Based on the IAA and its effect on seed vigor, 6KJ, 4PB and 2KB were selected for molecular identification. Results showed that the three isolates belonged to Bacillus genus, 6KJ as B. aryabhattai, 4PB belonging to B. cibi and 2KB having 97% homology with B. marisflavi. Further evaluation of the selected endophytic isolates producing IAA is necessary to be carried out to explore their potency as a source of hormone to promote plant growth.